Fixed Points Results for Various Types of Tricyclic Contractions - Mustapha Sabiri; Abdelhafid Bassou; Jamal Mouline; Taoufik Sabar (Axioms, 2021)
In this paper, we introduce four new types of contractions called in this order Kanan-S-type tricyclic contraction, Chattergea-S-type tricyclic contraction, Riech-S-type tricyclic contraction, Cirić-S-type tricyclic contraction, and we prove the existence and uniqueness for a fixed point for each situation.